Whole-Body MRI vs. PET/CT for the Detection of Bone Metastases in Patients With Prostate Cancer: A Systematic Review and Meta-Analysis - Zhan, Yuefu; Zhang, Guangming; Li, Mingliang; Zhou, Xiaobo (Frontiers in Oncology, 2021)
Purpose: A recent meta-analysis in patients with non-small cell lung cancer showed no difference between whole-body magnetic resonance imaging (WBMRI) and positron emission tomography/computed tomography (PET/CT), but no such study is available for prostate cancer (PCa). This study aimed to compare WBMRI and PET/CT for bone metastasis detection in patients with PCa. Materials and Methods: PubMed, Embase, and the Cochrane library were searched for papers published up to April 2020. The population was the patients with untreated prostate cancer diagnosed by WBMRI or PET/CT. The outcomes were the true positive and negative and false positive and negative rates for WBMRI and PET/CT. The summarized sensitivity, specificity, positive likelihood ratios (PLR), negative likelihood ratios (NLR), and diagnostic odds ratios (DOR) were calculated with their 95% confidence intervals (CIs). Results: Four prospective and one retrospective study are included (657 patients). Significant differences are observed between WBMRI and PET/CT for sensitivity (WBMRI/PET/CT: 0.896; 95% CI: 0.813–0.987; P = 0.025) and NLR (WBMRI/PET/CT: 2.38; 95% CI: 1.13–5.01; P = 0.023), but not for specificity (WBMRI/PET/CT: 0.939; 95% CI: 0.855–1.031; P = 0.184) and PLR (WBMRI/PET/CT: 0.42; 95% CI: 0.08–2.22; P = 0.305). WBMRI has a similar a DOR compared with PET/CT (WBMRI/PET/CT: 0.13; 95% CI: 0.02–1.11; P = 0.062). The summary area under the receiver operating characteristic curves for WBMRI is 0.88 (standard error: 0.032) and 0.98 (standard error: 0.013) for PET/CT for diagnosing bone metastases in PCa. Conclusion: PET/CT presents a higher sensitivity and NLR for the bone metastasis detection from PCa, whereas no differences are found for specificity and PLR, compared with WBMRI.